DISSECTING STUDENT MISCONSTRUCTION IN TRANSFORMATIONAL ACTIVITIES SOLVES PROBLEMS THAT ALLOW COGNITIVE CONFLICT TO OCCUR - Rosimanidar Rosimanidar; Purwanto Purwanto; Erry Hidayanto; I Made Sulandra (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The transformative activity was crucial for problem-solving. In resolving problems, cognitive conflicts could arise, characterized by construction errors marked by deviations or differences from scientific concepts. Eight of the 106 students who experienced cognitive conflicts made construction errors in transformative activities. These errors were categorized into four groups. This research aimed to describe students' construction errors in transformative activities when solving problems that might lead to cognitive conflicts. The research design was phenomenological, with four subjects selected and one student from each group. Student responses and interview results served as research data, analyzed through narrative text analysis. The research findings revealed four forms of construction errors in students during transformative activities in problem-solving that might lead to cognitive conflicts: (1) pseudo construction